The impact of social media on managing the image of the Polish national football team - Joanna Bańbuła; Zuzanna Kasperek (Sciendo, 2020)
Presented paper contains looks which mainly attempt to analyse the promotion in sport by social media and brand image management on the example of "Connected by football" channel.